Application of tree growing up algorithm to protein secondary structure estimation - Tuncer, Seda Arslan; Karci, Ali (Ieee Computer Soc, 2008)
In order to solve NP-type problems, a lot of methods have been developed by exploiting the properties of systems in the nature. Genetic Algorithms, Ant Colony Optimization, Artificial Neural Networks, Artificial Immune Systems, etc. are this-type algorithms. In this study, tree growing up algorithm inspired by growing up of trees was used to estimate the secondary structure of proteins. Proteins 1bbe, 1a89 and 1a9a were selected for experimental applications and obtained results illustrates the superiority of the applied method, since it obtained success of 99% based on the real-valued problems.
21st IEEE International Symposium on Computer-Based Medical Systems -- JUN 17-19, 2008 -- Jyvaskyla, FINLAND
Keywords: tree growing up algorithm; bioinformatics; protein structure estimation